Construction and application of knowledge-base in telecom fraud domain. (2nd March 2021) - Zhu, Rongchen; Ye, Han; Sun, Haichun; Li, Xin; Duan, Yongchen; Hou, Jiaqi
Nowadays, the number of telecom frauds crimes has been increasing rapidly in China. To improve the people's awareness of prevention and enhance the professional ability of public security police in investigating and combating, this paper proposes and implements a knowledge-base of the telecom fraud domain. Firstly, we improve the event-based telecom fraud ontology model by considering two perspectives, including crime combats and preventions. We also conduct a fine-grained classification and finish a multi-dimensional fusion of the domain knowledge to improve data quality. Secondly, we introduce a new method to reuse domain business processes knowledge, which is a supplementing of knowledge representation and enhances the quality of the knowledge-base. Finally, this paper shows two types of domain applications, a Q&A application and a case assistant. The experimental results show that the public and the police can get some advice and inspiration from the built knowledge-base.